Ca2+ permeability of unedited and edited versions of the kainate selective glutamate receptor GluR6. - Egebjerg, J (1993)
The Ca2+ permeability of the kainate selective glutamate receptor GluR6 depends on the editing of the RNA (or DNA). The unedited version of GluR6, GluR6Q, encodes a glutamine at position 621 (Q/R site) and exhibits a Ca2+/monovalent ion permeability ratio of 1.2, while the edited version of GluR6, GluR6R, encodes an arginine at position 621 and exhibits a permeability ratio of 0.47. Kainate activation of the GluR6 receptor results in currents that are modulated by extracellular calcium ions. Permeability ratios of other divalent ions indicate that the Q/R site is not the only determinant for divalent ion permeability. The level of editing of the receptor will determine the Ca2+ influx through the GluR6 receptor channels and, consequently, may modulate the synaptic activity.